2018
DOI: 10.3906/tar-1711-18
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective potential of the fruit (acorn) from Quercus coccifera L.

Abstract: Neurodegenerative diseases such as Alzheimer disease and Parkinson disease are among the deadly disorders affecting the elderly population. Unfortunately, effective treatments and medications are still needed to combat these diseases. The ethanol extracts of the raw peeled acorns and acorn coffees from Quercus coccifera prepared by two different methods (boiled-roasted ground and roasted ground) were tested against acetylcholinesterase (AChE), butyrylcholinesterase (BChE), and tyrosinase (TYR), the enzymes ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…AChE and BChE inhibitory activity of the samples was measured by slightly modified spectrophotometric method of Ellman et al (1961). All reagents, conditions and calculations were same as described in the previous publications (Senol et al, 2018;Gezici and Sekeroglu, 2019b). Briefly, electric eel AChE (EC 3.1.1.Sigma, St. Louis, MO, USA) and horse serum BChE (EC 3.1.1.…”
Section: Neuroprotective Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…AChE and BChE inhibitory activity of the samples was measured by slightly modified spectrophotometric method of Ellman et al (1961). All reagents, conditions and calculations were same as described in the previous publications (Senol et al, 2018;Gezici and Sekeroglu, 2019b). Briefly, electric eel AChE (EC 3.1.1.Sigma, St. Louis, MO, USA) and horse serum BChE (EC 3.1.1.…”
Section: Neuroprotective Activitymentioning
confidence: 99%
“…By now, anticancer, antiproliferative, anticholinesterase, antityrosinase, antioxidant, and other biological activities of numerous medicinal and aromatic plants (MAPs) and secondary metabolites isolated from MAPs were analysed in our laboratory (Akgunlu et al, 2016;Sekeroglu et al, 2017;Gezici et al, 2017;Belkhodja et al, 2017;Karik et al, 2018;Gundogdu et al, 2018;Senol et al, 2018;Gezici, 2018;Das et al, 2019;Shida et al, 2019;Gezici and Sekeroglu, 2019a;Gezici and Sekeroglu, 2019b;Gezici, 2019a;Gezici 2019b;Gezici, 2019, Sekeroglu et al, 2019 in press). Take into consideration our ongoing projects, evaluation cancer protective potentials against human cancer cells, investigating neuroprotective activities through enzyme inhibitions on acetylcholinesterase (AChE), butyrylcholinesterase (BChE), and TYR (tyrosinase) enzymes, along with determination of antioxidant capacities of extracts obtained from red hulls, kernels and oleo-gum resins of Pistachio (P. vera L.) are the main objectives of the presented research.…”
Section: Introductionmentioning
confidence: 99%
“…Table 5 presents source data relating to the use of the potential of bioactive ingredients found in acorns based on in vitro and in vivo studies. The results obtained by the authors indicate, among others, the possibility of using acorn extracts to inhibit selected enzymes (e.g., liver enzymes, enzymes stimulating the decomposition of neurotransmitters, or enzymes regulating the sugarinsulin metabolism) [120][121][122][123], heal skin wounds [124] or prevent inflammation (e.g., in gum diseases) [125]. The health-promoting properties of acorns are due to the presence of phytonutrients in them, among which the most important are phenolic compounds, triterpenes, sterols, tocopherols, and carotenoids [10,13].…”
Section: Historical and Potential Modern Uses Of Acorns In Medicinementioning
confidence: 87%
“…In agreement with these results, Senol et al (2011) and Skalicka-wozniak et al (2018) reported the cholinesterase inhibitory effect of xanthotoxin. Furthermore, many plants were reported to protect against AD through being a potential source of AChE inhibitors (Sekeroglu & Gezici, 2019;Şenol, Şekero glu, Gezıcı, Kiliç, & Erdo gan Orhan, 2018).…”
Section: Discussionmentioning
confidence: 99%